Blaming mothers : American law and the risks to children's health - Fentiman, Linda C., 1949- (Families, law, and society series., 2017)
In the past several decades, medicine, the media, and popular culture have focused on mothers as the primary source of health risk for their children, even though American children are healthier than ever. The American legal system both reflects and reinforces this conception of risk. This work explores how this occurs by looking at unconscious psychological processes, including the ways in which we perceive risk, which shape the actions of key legal decisionmakers, including prosecutors, judges, and jurors.